2020
DOI: 10.1111/jfb.14415
|View full text |Cite
|
Sign up to set email alerts
|

An encounter between a pelagic shark and giant cephalopod

Abstract: An oceanic whitetip shark (Carcharhinus longimanus) was observed off the coast of Kona, Hawaii, with scars caused by the tentacles of a large cephalopod. While the exact species could not be confirmed, candidate species include the giant squid (Architeuthis dux) or species from the genera Thysanoteuthis (flying squids) and Megalocranchia (glass squids). Telemetry shows C. longimanus will dive within the mesopelagic zone and may interact with or even forage for large cephalopods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…Wounds near the shark's mouth and trunk suggest a defensive response from squid to the white shark, although this could not be confirmed. The pattern and shape of the scars matches the suction cups on the arms and tentacles of cephalopods as observed in other shark species 17 . The estimation of the diameter of the most evident sucker marks in the shark WS11 ( Fig.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Wounds near the shark's mouth and trunk suggest a defensive response from squid to the white shark, although this could not be confirmed. The pattern and shape of the scars matches the suction cups on the arms and tentacles of cephalopods as observed in other shark species 17 . The estimation of the diameter of the most evident sucker marks in the shark WS11 ( Fig.…”
supporting
confidence: 77%
“…1a) allowed us to determine that the left side scar (≈ 20 cm long) had suction cups that measured 1-3 cm, while the length of the right side scar measured ≈ 60 cm long. Even though the cephalopod species could not be confirmed, observed marks from all analysed sharks could suggest an encounter with taxa such as the jumbo squid D. gigas, the neon flying squid O. bartramii, or the giant squid A. dux based on their potential distribution, arms and tentacles length, as well as the estimated size of the scars and suckers 12,[16][17][18] .…”
mentioning
confidence: 95%
“…Traveling-Midrange was more concentrated between the two main northern elephant seal colonies, and took place mainly at night and twilight hours. During night time, white sharks could take profit of the DSL rising from 350 to 500 m below to just a range of <200 m; in this sense, Becerril-García et al (2020) found squid tentacle fresh scars on the skin of white sharks from GuadalupeIsland, with strong evidence that these scars had appeared shortly since last observation; the access to these prey was also found byPapastamatiou et al (2020) with oceanic whitetip sharks, and LeCroizier et al (2020) confirmed the importance of mesopelagic prey contribution in Guadalupe's white shark diet. During dawn and sunset, this behavior possibly indicates a patrolling hunting strategy under low-light conditions, where the silhouette of the prey…”
mentioning
confidence: 89%
“…While the role of the island for this white shark population is unclear, evidence in previous studies showed that it can serve as a secondary nursery area for juveniles and as a feeding area for adults, which benefit from the pinniped colonies (mainly the northern elephant seal), although the frequency of attacks on them (seen at the surface) is not as high as in other areas such as California, which could be due to the excellent water clarity that allows ambush in deep waters (Domeier et al, 2012;Hoyos-Padilla et al, 2016;Skomal et al, 2015). Moreover, according to new evidence (Becerril-García et al, 2020;Le Croizier et al, 2020;Papastamatiou et al, 2020), Guadalupe Island could be more important than previously thought in terms of access to mesopelagic prey, acting as a barrier trap and hindering their dispersion.…”
Section: Unlike Many Other White Shark Aggregation Sites Guadalupementioning
confidence: 99%
“…), glass squid (Megalocranchia spp. ), or giant squid (Papastamatiou et al, 2020). The colossal squid (Mesonychoteuthis hamiltoni) has hooks along the length of its arms and larger, revolving 'club hooks' at the tips of its tentacles, which are believed to be used in prey capture, but may also be used in self-defence (Rosa et al, 2017).…”
Section: Retaliatory Responsesa Last Resortmentioning
confidence: 99%